Effects of active and passive smoking on salivary cytokines levels in rats: A pilot study. (February 2019) - Ge, Sheng; Ye, Pei; Li, Guo-Yang; Fu, Yi-Fu; Zhou, Qian; Huang, Fan; Wang, Xiang; Wang, Wen-Mei
Cigarette smoking is an established risk factor for some oral diseases. As an essential fluid in the oral cavity, saliva is crucial to maintain oral health. Relative to active smoking, there are very few studies assessing the effect of passive smoking on salivary cytokines levels. In the present study, we established the rat models by the means of the intraoral cigarette smoking or whole body cigarette smoke exposure to simulate human active or passive smoking, respectively. The effects of active or passive smoking on salivary cytokines levels were assessed by using ProcartaPlex multiplex immunoassays. The results of the current study indicated that both active and passive smoking diminished the body weights of rats and increased the levels of some blood counts. Intriguingly, active smoking enhanced the salivary levels of IL-6 and IL-12 p70 and passive smoking elevated the salivary IL-6 level. Moreover, active smoking appeared to have a more prominent activation effect on the salivary IL-6 level. It was noted that active or passive smoking had no significant effect on the salivary IFN-γ level. Active or passive smoking could have potential effects on the salivary levels of some pro-inflammatory cytokines.